Glucagon-like peptide-1 (GLP-1) agonists in the treatment of obesity - Mazurek, Magdalena; Białowąs, Edyta; Dybała, Ewelina; Cuber, Iwona; Aghadi, Artur (Journal of Education, Health and Sport, 2023)
Background: Obesity is an increasing problem in the modern world due to increased morbidity and due to its clinical consequences. It is a chronic disease that causes the development of numerous complications, such as cardiovascular diseases, type 2 diabetes or cancer. The problem of the excessive body weight is global and affects over 2 billion people around the world. Due to the increasing problem of obesity, pharmacotherapy is recommended in patients with BMI ≥30 kg/m2 or BMI ≥27 kg/m2 with accompanying risk factors. To fight obesity, however, we primarily use lifestyle modification methods, such as a rational and balanced diet based on reduced caloric content and a low-carbohydrate diet. Another aspect is the use of the optimal amount of exercise of moderate intensity. Only the combination of all these methods gives a real chance for long-term weight loss and maintenance. Scientific research on GLP-1 analogue drugs such as semaglutide and liraglutide brings us a lot of prospects. The mechanism of their action is based on mimicking the natural GLP-1 secreted in the body. Aim of the study: The following article as an analysis of the current medical knowledge on the effectiveness and safety of obesity treatment with GLP-1 agonists based on available publications. Methods and materials: Literature review based on PubMed data using the following key words: obesity; semaglutide; Glucagon-like peptide-1 (GLP-1) agonists State of knowledge: GLP-1 receptor agonists are incretin drugs. This class of drugs has been approved by the FDA for the treatment of type 2 diabetes. Results: Numerous studies have shown that chronic systemic delivery of GLP-1 agonists led to weight loss and helped to maintain a lower body weight. Reduction in food intake is reported as the main mechanism.